Self-esteem and communication disturbances in schizophrenic patients - Lepeškienė, V. (Psichologija, 1990)
The present paper is concerned with the disturbances in the communication processes of the patients with mild cases of schizophrenia. The results of the . investigation have shown that selfesteem of those patients is much lower than that of the control group and that those patients feel themselves much more anxious in social situations than healthy persons. It proves the idea that social isolation of these patients is a defensive behaviour, caused by their sttiving to avoid "psychological threat" to their self-esteem.
Keywords: schizophrenia; self-esteem; communication disturbances